Arterial hypertension in women: state of the art and knowledge gaps - Chapman, Niamh; Ching, Siew M.; Konradi, Aleksandra O.; Nuyt, Anne Monique; Khan, Taskeen; Twumasi-Ankrah, Betty; Cho, Eun J.; Schutte, Aletta E.; Touyz, Rhian M.; Steckelings, U. Muscha; Brewster, Lizzy M. (Lippincott Williams and Wilkins, 2023)
Hypertension is the leading risk factor for cardiovascular disease and premature death among women globally. However, there is a fundamental lack of knowledge regarding the sex-specific pathophysiology of the condition. In addition, risk factors for hypertension and cardiovascular disease unique to women or female sex are insufficiently acknowledged in clinical guidelines. This review summarizes the existing evidence on women and female-specific risk factors and clinical management of hypertension, to identify critical knowledge gaps relevant to research, clinical practice, and women's heart health awareness. Female-specific risk factors relate not only to reproduction, such as the association of gynecological conditions, adverse pregnancy outcomes or menopause with hypertension, but also to the specific roles of women in society and science, such as gender differences in received medical care and the underrepresentation of women in both the science workforce and as participants in research, which contribute to the limited evidence-based, gender- or sex-specific recommendations. A key point is that the development of hypertension starts in young, premenopausal women, often in association with disorders of reproductive organs, and therefore needs to be managed early in life to prevent future cardiovascular disease. Considering the lower blood pressure levels at which cardiovascular disease occurs, thresholds for diagnosis and treatment of hypertension may need to be lower for women.